Feeding strategies alter gene expression of the calpain system and meat quality in the longissimus muscle of Braford steers - Coria, Maria Sumampa (2019)
Objective: The aim of the present study was to determine the effect of supplementing pasture-finished steers with corn silage on the expression level of the calpain system proteins and beef tenderization. Methods: Thirty Braford steers grazing on summer pasture were used for the study. For 120 days fifteen animals were supplemented with corn silage at 1% of body weight per head per day (Suppl) whereas the remaining 15 steers only received pasture (Contr). Carcass and meat traits were evaluated and compared between groups. Gene expression and activities of proteases (calpain 1 and calpain 2) and inhibitor (calpastatin) were measured using real-time polymerase chain reaction and casein zymography. Results: Carcass and meat traits were significantly different between feeding systems. Supplemented steers showed higher hot carcass weight (p<0.01), fat content (p = 0.02), and Warner-Bratzler shear force (p = 0.03). Furthermore, the control group showed higher protease:inhibitor ratios, at mRNA (p = 0.01) and protein levels (p<0.10). Warner-Bratzler shear force and mRNA calpains:calpastatin ratio were associated in both feeding systems (p<0.01). Conclusion: Based on the results obtained in the study, beef tenderness differences among finishing strategies could be modulated through differential expression of the calpain system proteins.